The Effectiveness of Evaluation of Mathematics Learning Using Wordwall Media in Elementary School - Shafwa, Emira; Hikmat, Ade (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study aims to determine the effectiveness of learning mathematics at the time of evaluation. The type of research used is a Quantitative Experiment. The method used in this research is a quantitative experiment using a design that is a quasi-experimental post-test type only with a nonequivalent group design. The sampling technique used is Cluster Random Sampling. The subjects of this study were 28 students in grade 4 at SD Muhammadiyah 2 Jakarta from 158 students of the population at SD Muhammadiyah 2 Jakarta. The result of this study were (1) The results of validity about Wordwall media in the student response questionnaire, which is a closing learning activity or arguably an evaluation of learning mathematics material for a fraction of numbers, is very effective with an average value of 69.1 questionnaires (2) Using paper media to get an average result of 50.00 was not effective (3) Using Wordwall media to get an average result of 77.14 was very effective from the above result mathematics learning at SD Muhammadiyah 2 Jakarta.